EVALUASI PENCATATAN KEUANGAN USAHA KECIL BERBASIS INTERNET - Shaferi, Intan (Faculty of Economics and Business Universitas Jenderal Soedirman, 2015)
This research aims to know how financial information was recorded by the smallbusinesses internet based. Survey method used to collect the data. Sample was choosenby purposive sampling for thirty small online businesses during two months.The result shows that in general that small businesses already implemented thebasic record from assets, liabilities, and equity, but the characteristic of quality needs alot of improvement.